Efficient thermal management of Li-ion batteries with a passive interfacial thermal regulator based on a shape memory alloy. (October 2018) - Hao, Menglong; Li, Jian; Park, Saehong; Moura, Scott; Dames, Chris
Abstract The poor performance of lithium-ion batteries in extreme temperatures is hindering their wider adoption in the energy sector. A fundamental challenge in battery thermal management systems (BTMSs) is that hot and cold environments pose opposite requirements: thermal transmission at high temperature for battery cooling, and thermal isolation at low temperature to retain the batteries' internally generated heat, leading to an inevitable compromise of either hot or cold performances. Here, we demonstrate a thermal regulator that adjusts its thermal conductance as a function of the temperature, just as desired for the BTMS. Without any external logic control, this thermal regulator increases battery capacity by a factor of 3 at an ambient temperature (T ambient ) of −20 °C in comparison to a baseline BTMS that is always thermally conducting, while also limiting the battery temperature rise to 5 °C in a very hot environment (T ambient  = 45 °C) to ensure safety. The result expands the usability of lithium-ion batteries in extreme environments and opens up new applications of thermally functional devices. Thermal fluctuations inside batteries limit their performance and pose various safety hazards. Here, the authors develop a shape memory alloy-based thermal regulator that stabilizes battery temperature in both hot and cold extreme environments.